Formação de um ecossistema de inovação o caso da cidade de Florianópolis - Garay, Jerusa Garcia (Universidade do Vale do Rio dos Sinos, 2019)
The Innovation Ecosystem model has been emerging as a valuable alternative in city development, particularly in the face of the challenges brought about by deindustrialisation and population growth. In spite of that, there are still many gaps in our understanding of this emerging phenomenon, both as regards the appropriate use of the term, as well as the necessary requirements for the development of such ecosystems. It must be said that the most renowned cases are related to cities located in developed countries. By means of a single-case study carried out in the city of Florianopolis, southern Brazil, the present research has analyzed the dynamics of collaborative actions towards the creation of an innovation ecosystem in that city, in the light of the theory of Knowledge-based Development, by applying the Capital System. To this end, the qualitative method was adopted, with a processual approach. Data collection was conducted through semi-structured interviews, document research and observation. As the chief analysis strategy, narrative, temporal bracketing and visual maps have been employed. Thus, the four phases that occurred for creation of the ecosystem have been identified. For each of them, the knowledge capitals involved was pointed out, as well as the relationship dynamics between them. It was also shown how different actors (the government, the university, industry and civil society) have contributed to this process. Among the main findings of our research is the acknowledgement that all these capitals are present in all four phases and that they manifest themselves gradually throughout. Moreover, the relevance of Relational Capital for the mobilization of the other capitals was corroborated, as was the significance of Identity Capital. The present study contributes with the proposition of a Dynamic Model for the Capital System, a model which represents the relationship between capitals in the process of creating an ecosystem. Therefore, our research offers contributions to the literature on Knowledge-based Development, thus strengthening the potential for the application of the Capital System and bringing it closer to the literature on ecosystems. The adoption of the processual method also represents a relevant input to the study of innovation ecosystems, as well as to the theoretical field of Knowledge-based Development.
Keywords: Ecossistemas de Inovação; Sistema de Capitais; Cidades; Desenvolvimento baseado no Conhecimento; Innovation Ecosystem; Capital System; Cities; Knowledge-based Development; ACCNPQ::Ciências Sociais Aplicadas::Administração